Gender and Organizational Process: Community Collective Identities in the Western Region of Costa Rica - Tasies Castro, Esperanza (2020)
This article discusses the results of an investigation on the organizational processes developed by women in community spaces of the Western Region of Costa Rica. As a result of this research effort, a typology of these community organizations has been elaborated, distinguishing the relationships between ends and means that these groups strategically establish. Because of its qualitative approach interested in generation of formal theory, this research has constructed a conceptualization and contextualization of the organizational process and collective identities that explain the existence of 41 women's community organizations in five cantons of the Western Region